2020
DOI: 10.1016/s2542-5196(20)30103-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of outdoor fine particulate air pollution and cardiovascular disease in 157 436 individuals from 21 high-income, middle-income, and low-income countries (PURE): a prospective cohort study

Abstract: Background Most studies of long-term exposure to outdoor fine particulate matter (PM 2•5 ) and cardiovascular disease are from high-income countries with relatively low PM 2•5 concentrations. It is unclear whether risks are similar in low-income and middle-income countries (LMICs) and how outdoor PM 2•5 contributes to the global burden of cardiovascular disease. In our analysis of the Prospective Urban and Rural Epidemiology (PURE) study, we aimed to investigate the association between long-term exposure to PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 33 publications
3
71
3
3
Order By: Relevance
“…Combining stroke subtypes may have contributed to the observed weaker associations for stroke. The PM 2:5 levels observed in this study reflect average ambient exposure levels observed in the contiguous United States between 1988 and 2008, whereas other geographic regions may experience higher average ambient PM 2:5 levels (Hystad et al 2020;Lee et al 2018). These findings may not be generalizable to populations exposed to higher levels of long-term ambient PM 2:5 exposure.…”
Section: Discussioncontrasting
confidence: 61%
“…Combining stroke subtypes may have contributed to the observed weaker associations for stroke. The PM 2:5 levels observed in this study reflect average ambient exposure levels observed in the contiguous United States between 1988 and 2008, whereas other geographic regions may experience higher average ambient PM 2:5 levels (Hystad et al 2020;Lee et al 2018). These findings may not be generalizable to populations exposed to higher levels of long-term ambient PM 2:5 exposure.…”
Section: Discussioncontrasting
confidence: 61%
“…The main contributors to the higher estimates in GBD 2019 are the inclusion of disease burden attributable to air pollution mediated by low birthweight and short gestation, and updated relative risk curves, particularly for stroke, with the availability of recent evidence, including from India. 26 , 43 , 44 , 45 These method updates resulted in an increased estimate of the burden attributable to air pollution in India, which accounted for an estimated 1·67 million deaths in India in 2019. For comparison with the estimate of 1·24 million (1·09–1·39) air pollution attributable deaths in India in 2017 in GBD 2017, 21 the 2017 estimate for India in GBD 2019 is 1·60 million (1·41–1·80) deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid artery stenosis, one of the risk factors for ischemic stroke, is also reported to be independently associated with increasing PM2.5 concentration 21 . Population attributable risk factor for PM2.5 was highest for stroke (19.6%) as compared to other cardiovascular diseases in a large multinational cohort study 22 .…”
Section: Discussionmentioning
confidence: 90%